A review on nutrients, phytochemicals, and health benefits of green seaweed, caulerpa lentillifera - Nur Syakilla; Ramlah George @ Mohd. Rosli; Chye, Fook Yee; Wolyna Pindi; Sylvester Mantihal; Noorakmar Ab Wahab; Fazlini Mohd Fadzwi; Philip Huanqing Gu; Patricia Matanjun (MDPI, 2022)
Caulerpa lentillifera is a type of green seaweed widely consumed as a fresh vegetable, specifically in Southeast Asia. Interestingly, this green seaweed has recently gained popularity in the food sector. Over the last two decades, many studies have reported that C. lentillifera is rich in polyunsaturated fatty acids, minerals, vitamins, and bioactive compounds that contribute many health benefits. On the other hand, there is currently hardly any article dedicated specifically to C. lentillifera regarding nutritional composition and recent advancements in its potential health benefits. Hence, this study will summarise the findings on the nutritional content of C. lentillifera and compile recently discovered beneficial properties throughout the past decade. From the data compiled in this review paper, it can be concluded that the nutrient and phytochemical profile of C. lentillifera differs from one region to another depending on various external factors. As a result, this paper will offer researchers the groundwork to develop food products based on C. lentillifera. The authors of this paper are hopeful that a more systematic review could be done in the future as currently, existing data is still scarce.